Vizuální řeč ovladačů a sdělovačů obráběcích strojů v Československu z let 1947-1990 - Fridrichová, Eva (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Tato dizertační práce se zabývá vývojem provozní grafiky na ovládacích panelech obráběcích strojů Továren obráběcích strojů z let 1947–1990. Cílem je popis geneze grafiky ovladačů a sdělovačů obráběcích strojů a jejich zařazení do kontextu vývoje provozní grafiky, dále také zjištění vlivu designu na oblast provozní grafiky. Tato oblast dosud nebyla podrobena bližšímu zkoumání a z hlediska ucelení historických aspektů české provozní grafiky je přínosem do budoucna.

This thesis deals with the development of graphical symbols on the control panels of machine tools made by Czech factories TOS from the years 1947–1990. The aim is description genesis graphics controllers and communicators of machine tools and their inclusion in the context of the development of graphic design. As well as determine the influence of design in area of operational graphics. This area has not yet been subjected to closer examination and in terms of consistency of the historical aspects of the Czech graphic is benefit to the future.
Visual Language of Controllers and Communicators of Czechoslovak Machine Tools in 1947-1990
Keywords: design; grafika; symboly; ovládače; sdělovače; historie; obráběcí stroje; design; graphics; symbols; controllers; communicators; history; machine tool